Acute toxicity, anti-inflammatory and antinociceptive investigations of extracts from Ampelocissus africana (Lour) Merr (Vitaceae) rhizomes - Wendkouni Leila Marie Esther Belem-Kabré; Noufou Ouédraogo; Adjaratou Compaoré-Coulibaly; Mariam Nebié-Traoré; Tata Kadiatou Traoré; Sylvain Ilboudo; Constantin Boladé Atchadé; Abdoul Gilchrist Laurent Boly; Marius Lompo; Martin Kiendrebeogo; Sylvin Ouédraogo (International Journal of Phytomedicine, 2020)
Ampelocissus africana (Lour) Merr (Vitaceae) is a plant used in traditional medicine in Burkina Faso in the treatment of wounds, edema, drops, infections. This study focused on pharmacological investigations effects of methanolic and aqueous extracts from Ampelocissus africana (Lour) Merr rhizomes. The acute toxicity of the extracts from Ampelocissus africana was performed under OECD 423 guidelines. The anti-inflammatory activity was evaluated in vivo using carrageenan-induced paw edema of mice at the doses to 50, 100, 200, 400, 600 mg/kg body weight (bw). The antinociceptive activity of the extracts was determined using acetic acid, formalin nociception models in mice at the doses to 50, 100, 200, 400 and 600 mg/kg bw. The involvement of ATP-sensitive K+ channel pathway and opioid system were tested using glibenclamide, and naloxone respectively at the unique dose (400 mg/kg). No mortality of mice were observed at dose of 2000 mg/kg b.w. The lethal dose (LD50) value estimated to 5000 mg/kg b.w. The tests were showed that the extracts exerted significant dose-dependent anti-inflammatory responses in the paw induced by carrageenan (from 37 to 72.90 percent inhibition), antinociceptives in acetic-induced abdominal contractions (from 25.10 to 63.08%), and in formaldehyde-induced paw licking (from 9.27 to 71.77%) tests. The pretreatment with naloxone and glibenclamide did not affect the antinociceptives effects. The results suggested that the extracts from the rhizomes of Ampelocissus africana possessed anti-inflammatory and antinociception effects in mice. These effects could justify the uses of this plant in traditional medicine.